The origin of mind : evolution of brain, cognition, and general intelligence - Geary, David C. (American Psychological Association, 2005)
This book sets out a comprehensive, integrated theory of why and how the human mind has developed to function as it does. Geary proposes that human motivational, affective, behavioral, and cognitive systems have evolved to process social and ecological information (e.g., facial expressions) that covaried with survival or reproductive options during human evolution. In this view, Darwin's conceptualization of natural selection as a "struggle for existence" becomes, for us, a struggle with other human beings for control of the available resources. This struggle provides a means of integrating modular brain and cognitive systems such as language with those brain and cognitive systems that support general intelligence. To support his arguments, Geary draws on an impressive array of recent findings in cognitive science and neuroscience as well as primatology, anthropology, and sociology. Geary also explores a number of issues that are of interest in modern society, including how general intelligence relates to academic achievement, occupational status, and income.